Violence against women and femicide - Piedra Durán, Marcela (2020)
This article is a result of the findings of the research project "Femicide: The Extreme Expression of Violence Against Women". It’s objective is to expose the violence against women and femicide as a result of the power inequalities generated and legitimized by patriarchal structures The theoretical discussion about the concept of femicide and how it is reflected in the country’s statistics not only highlight the femicide as a public interest matter, but also the need to include it in all the  violence prevention policies developed in Costa Rica.